Analysis and Investigation of a Novel Microwave Sensor with High Q-Factor for Oil Sensing - Ammar Alhegazi; Zahriladha Zakaria; Noor Azwan Shairi; Tole Sutikno; Rammah A. Alahnomi; Ahmed Ismail Abu-Khadrah (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this paper, a novel microwave sensor with high Q-factor for oil sensing is analyzed and investigated. The new design is based on a gap waveguide cavity resonator (GWCR). To characterize and evaluate the sample, the oil under tested (OUT) is injected into a Teflon tube, which is passing through the microfluidic channel that is located in the middle of the cavity where the electric field concentrates. The results show that the proposed sensor has a high Q-factor of 4832. Moreover, the proposed design has the ability to sense and detect different types of oils with a small variation of permittivities such as Fish oil, Coconut oil, Olive oil, Linseed oil and Castor oil. The permittivity equation is extracted using the polynomial fitting method to define unknown dielectric properties of the OUT. The results show that the evaluated permittivity using the proposed sensor has a good agreement with the ideal permittivity. Therefore, the proposed sensor is a good candidate for oil processing in food industries.